Large Scale Implementation of Question Mark Perception (V2.5). Experiences at Loughborough University - Myles Danson; Brian Dawson; Tim Baseley (2001)
The paper outlines the experiences to date of two projects dealing with Question Mark Perception (V2.5) (http://www.qmark.com/perception/index.html). The first has been funded through the Teaching Quality Enhancement Fund (TQEF) and aims to implement a centrally supported web based CAA system to be offered to all staff at Loughborough University. This TQEF CAA project began in September 1999 and ends September 2002. The second project is funded by the Joint Information Systems Committee (JISC) Committee for Integrated Environments for Learners (JCIEL). This project aims to integrate the central web based assessment system with various management information systems (MIS) making a step towards the emergence of a Managed Learning Environment (MLE). This JISC CAA MLE project began October 2000 and ends September 2002. We outline the rational, progress to date, issues arising, problems encountered and solved, and should be of interest to any institution considering a large scale roll out of Question Mark Perception. The deliverable of this JISC Project will be documentation detailing the experiences of the project and being generic in nature where possible. We will include the administrative, technical and pedagogical issues faced. Solutions and examples will be offered as appropriate. This document should be of use to any institution considering similar work. The final document will be available at the end of the project, September 2002, and will be disseminated by the JISC / JCIEL free to any UK HEI.